Criteria for Assessment of Cognitive Impairment in Clinical Trials - A. P. Solovyova; D. V. Goryachev; V. V. Arkhipov (Регуляторные исследования и экспертиза лекарственных средств)
Neuropsychological research methods are used to evaluate cognitive functions (CF). Tests used in clinical neuropsychology, in most cases, describe one or more aspects of cognitive domains that are theoretical «constructs» in which several cognitive processes are involved. Neuropsychological tests measure CFs regardless of the medical condition of the test subject. This allows for determination of even minor changes in CFs, including in clinical trials, which is of fundamental importance in studying the efficacy and safety of a given therapy. This article deals with specific aspects of using neuropsychological and screening testing of cognitive functions in individual domains on the basis of foreign experience. It discusses the criteria for selection and application of individual tools, their features, and choice of criteria for evaluating the results of testing in clinical studies in cases of CFs deterioration in various medical conditions accompanied by cognitive impairment. When planning clinical trials, it should also be taken into account that mixed anxiety-depressive disorders are likely to cause forgetfulness, and this calls for differential diagnosis and should be registered in clinical research protocols. The use of subscales and combinations of components of different tools are encouraged based on the objectives of the clinical study, and the tools of neuropsychological research and cognitive function assessment should be validated taking into account the specificity and sensitivity of the method, using statistical analysis methods for specific purposes and tasks. Such a multifaceted approach to the study of cognitive impairments will significantly increase the level of clinical trials conducted and, consequently, will make it possible to put up for sale efficacious and safe medicines for the treatment of cognitive impairment.